Electrocardiographic parameters in Holstein calves reared at high altitude and at sea level - Begazo C., Christian (2017)
The aim of the study was to compare the electrocardiographic parameters of clinically healthy Holstein calves raised in the high altitude (3827 m) and at sea level (175 m). Parameters under evaluation were rate, rhythm, size and morphology of the waves, segments and intervals and cardiac axis. The tests were performed in an upright position at an amplitude of 1 mV/cm and speed of 25 mm/sec, using the bipolar (I, II, III) and unipolar (AVL, AVR, and aVF) leads. The results showed that heart rate was 87.33 ± 9.77 and 127.40 ± 7.52 at high altitude and at sea level respectively. The heart rate at both locations were considered as regular normal sinus rhythm. The cardiac axis at high altitude was -120.1 ± 7.30° and at sea level was 63.7 ± 3.02°. It is concluded that there were statistical differences (p<0.05) in heart rate, size and morphology of the waves, intervals, segments and cardiac axis due to the physiological adaptation to the high altitude